1994
DOI: 10.1002/lsm.1900150204
|View full text |Cite
|
Sign up to set email alerts
|

Determination of efficient parameters for argon laser‐assisted anastomoses in rats: Macroscopic, thermal, and histological evaluation

Abstract: The aim of this study was to determine efficient parameters for an argon laser (spot diameter = 200 microns) to obtain and reproduce vessel anastomoses. It was performed in two groups of Wistar rats. In the first group (89 Laser impacts on 10 carotids), the fluence was continuously adjusted from 30 to 3,000 J/cm2 in order to determine efficient sets of parameters (power from 90-200 mW, pulse duration from 0.1 to 5 seconds, pulsed or continuous mode). In the second group, 30 end-to-end carotid anastomoses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…White, Kopchok, and others [2][3][4] confirmed this fact with argon laser welding of vessels, but they proposed that collagen was not denatured after argon laser irradiation. However, other investigators [5,6] using the same laser type demonstrated that collagen denaturation had occurred. Brooks et al [7], using a histological technique with picrosirius red F3BA staining, confirmed that vascular tissue was denatured in argon laser welding.…”
Section: Introductionmentioning
confidence: 93%
“…White, Kopchok, and others [2][3][4] confirmed this fact with argon laser welding of vessels, but they proposed that collagen was not denatured after argon laser irradiation. However, other investigators [5,6] using the same laser type demonstrated that collagen denaturation had occurred. Brooks et al [7], using a histological technique with picrosirius red F3BA staining, confirmed that vascular tissue was denatured in argon laser welding.…”
Section: Introductionmentioning
confidence: 93%
“…A similar tissue vaporization is seen in HIFU tissue emulsification, although tissue carbonization is less likely to occur as desiccated tissue cannot propagate ultrasound, and further heating does not occur beyond this point. Successful vascular occlusion by collagen fusion occurs in temperature range 73-878C [57], while temperatures below 548C caused no structural changes in collagen [57].…”
Section: Effect Of Heating On Vessels and Highintensity Focused Ultramentioning
confidence: 99%
“…For example, the infrared CO2 laser wavelength (λ = 10,600 nm) is predominantly absorbed by water, resulting in a superficial OPD, whereas the visible and near-infrared wavelengths of diode lasers (λ = 670-988 nm) exhibit a significantly greater OPD in tissue. The absorption of some lasers can be selectively enhanced by pigment molecules (i.e., hemoglobin and melanin) [20,21,30,36,72,77] or exogenous dyes, such as indocyanine green (ICG) [78] and fluorescein isothiocyanate [53]. The degree of heat build-up is determined by the laser irradiance (W/cm 2 , i.e., power output (W) / spot area (cm 2 )), radiant exposure (J/cm 2 , irradiance × irradiation time (s)), and the lasing mode (i.e., continuous or pulsed mode).…”
Section: Laser-tissue Interactionsmentioning
confidence: 99%
“…Unfortunately, several drawbacks associated with current (native) LAVW techniques [6,18,20,26,34,44,45] have hampered its transition from the experimental to the clinical setting [40,44,45]. First, the relatively low welding strengths produced with LAVW often require additional sutures to reinforce the anastomosis, ultimately defeating the purpose of the modality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation